Dark-Field Imaging: Recent developments and potential clinical applications. Issue 12 (December 2016) - Ando, Masami; Sunaguchi, Naoki; Shimao, Daisuke; Pan, Adam; Yuasa, Tetsuya; Mori, Kensaku; Suzuki, Yoshifumi; Jin, Ge; Kim, Jong-Ki; Lim, Jae-Hong; Seo, Seung-Jun; Ichihara, Shu; et al.
Highlights: "X-ray Dark-Field Imaging" technique and associated optics was proposed in 2002. This optics provides high contrast and high spatial resolution X-ray images. A variety of 2-D, 2.5-D and 3-D imaging paradigms using this optics have been presented. Applications of the X-ray Dark-Field optics to medical imaging, including the first 3-D images, have been presented. Abstract: This paper describes an X-ray phase contrast imaging technique using analyzer-based optics called X-ray Dark-Field Imaging that has been under development for the past 10 years. We describe the theory behind XDFI, the X-ray optics required for implementing it in practice, and algorithms used for 2D, 2.5D, and 3D image reconstruction. The XDFI optical chain consists of an asymmetrically cut, Bragg-type monochromator-collimator that provides a planar monochromatic X-ray beam, a positioning stage for the specimens, a Laue-case angle analyzer, and one or two cameras to capture the dark and bright field images. We demonstrate the soft-tissue discrimination capabilities of XDFI by reconstructing images with absorption and phase contrast. By using a variety of specimens such as breast tissue with cancer, joints with articular cartilage, ex-vivo human eye specimen, and others, we show that refraction-based contrast derived from XDFI is more effective in characterizing anatomical features, articular pathology, and neoplastic disease than conventional absorption-based images. For example, XDFI of breast tissue can discriminate between the normal and diseased terminal duct lobular unit, and between invasive and in-situ cancer. The final section of this paper is devoted to potential future developments to enable clinical and histo-pathological applications of this technique.